A Critical Review of Social Protection Policies, Programs and their Effectiveness in Nepal - Khanal, Dilli Raj (Nepalese Journal of Insurance and Social Security, 2018)
The objective of the paper is to review the existing literature on social security and social protection program in Nepal carried out by Government of Nepal and offered suggestion for the betterment of the program in the line of equality, financial sustainability and economic growth. The paper is prepared based on the desk review of the various scientific articles and report published by the institutions and individual authors. In total 64 papers have been reviewed published during ten years period ranges from 2006 to 2015. Based on the critical review the paper conclude that Dalits, endangered community, school girls, child and people living in the remote areas such as Karnali have been benefitted from numerous social security related programs. The doubling of social assistance is enhancing social protection of those who are in such nets. However, social security programs lack effectiveness compared to increased budget, scattered programs implemented through different agencies in many instances in an adhoc basis without effective coordinated implementation mechanism has made the outcomes less beneficial and effective from the standpoint of intended beneficiaries. One of the serious challenges in the areas of social security is that still all workers working in the informal economy consisting of more than 96 per cent of the total labor force are outside the purview of social security program. The new Integrated Social Security act has also not covered the workers in the informal sector. Similarly, it encompasses through many ambiguities and overlaps. A big chunk of entitled population is deprived of getting the benefits of such programs. More worryingly, out of them, most deprived are disabled.